THE STRATEGIC ROLE OF PUBLIC RELATIONS IN THE ERA OF AI AND PR 4.0 - Iwan Santosa (TOPLAMA, 2026)
Public relations (PR) holds a crucial role in managing the reputation and image of higher education institutions. In the era of Industry 4.0 and Society 5.0, characterized by the dominance of technology, the presence of artificial intelligence (AI) has a significant impact on the realm of PR, giving rise to the term “PR 4.0.” This qualitative systematic literature review examines the role of public relations in higher education institutions in the era of PR 4.0 in terms of the strategic aspects and methods applied by higher education PR practitioners. This study revealed that there’s a disparity in the paradigm and practice of PR management in higher education institutions as a strategic and technical operational function. Indonesian universities have generally implemented cyber PR utilizing new media and corporate communication models that are considered effective. Several institutions have also utilized AI as a supplementary tool in their public relations activities.